МАЛАЙЗИЯ ДАВЛАТИДА ИЖТИМОИЙ-МАЪНАВИЙ МУҲИТ ҲОЛАТИ - Кахарова, М. (SCIENCE and SOCIETY, 2023)
This article describes the state of the social and spiritual environment in Malaysia and the activities of organizations that serve to improve the mental health of the population. Traditions and values, social and spiritual life of the population were also analyzed.
Keywords: globalization; crisis; ideology; spirituality; idea; state; family; elderly; symbols; national mentality; people; thinking; Japanese spirit; ethnic group; threat